Marketing analytics statistical tools for marketing and consumer behaviour using SPSS - Mesquita, José Marcos Carvalho de; Kostelijk, Erik. (bingdon, Oxon New York, NY Routledge, 2022)
Marketing Analytics provides guidelines in the application of statistics using SPSS for students and professionals studying quantitative methods in Marketing and Consumer Behaviour. With simple language and a practical, screenshot-led approach, the book presents eleven multivariate techniques and the steps required to perform analysis. Each chapter contains a brief description of the technique, followed by the possible marketing research applications. One of these applications is then used in detail to illustrate its applicability in a research context, including the needed SPSS commands and illustrations. Each chapter also includes practical exercises, which require the readers to perform the technique and interpret the results, equipping students with the necessary skills to apply statistics, by means of SPSS, in marketing and consumer research. Finally, there is a list of articles employing the technique, which can be used for further reading. This textbook provides introductory material for advanced undergraduate and postgraduate students studying marketing and consumer analytics, teaching methods along with practical software-applied training using SPSS. Support material includes two real datasets to illustrate the techniques' applications and PowerPoint slides providing a step-by-step guide to the analysis and commented outcomes"--
Includes bibliographical references and index.
Keywords: Marketing -- Data processing; Marketing -- Statistical methods